Temporal Relation Between Myocardial Infarction and New-Onset Atrial Fibrillation: Results from a Nationwide Registry Study - Karlsson Elin; Kiviniemi Tuomas; Halminen Olli; Lehtonen Ossi; Teppo Konsta; Haukka Jari; Mustonen Pirjo; Putaala Jukka; Linna Miika; Hartikainen Juha; Airaksinen K.E. Juhani; Lehto Mika; et al. (United States, 2025)
Myocardial infarction (MI) and atrial fibrillation (AF) are commonly seen in the same patient. In this study, we evaluated the temporal relations and prognosis of MI and AF. This is a substudy of the nationwide registry-based Finnish Anticoagulation in Atrial Fibrillation (FinACAF) study, comprising all Finnish patients with new-onset AF from 2010 to 2017. Patients with MI and AF were divided into groups depending on the temporal relation between the disease onsets: (1) MI before AF (MIAF), and (4) no MI. The 1-year mortality in the groups were studied with the Cox proportional hazards model. Of the 153,207 patients with new-onset AF (mean age 72.7 years, 50.0% women), 16,265 (10.6%) were diagnosed with MI. Altogether, 8,889 (54.7%) of the patients with MI were in the MIAF group. Of all MIs, 42.2% were diagnosed within 1 year from new-onset AF. The MI>AF group had the worst survival, with an adjusted hazard ratio for death of 3.08 (confidence interval [CI] 2.89 to 3.27) compared with patients without MI. For the MI